Oncogenic RAS Mutants Confer Resistance of RMS13 Rhabdomyosarcoma Cells to Oxidative Stress-Induced Ferroptotic Cell Death - Schott, Christina; Graab, Ulrike; Cuvelier, Nicole; Hahn, Heidi; Fulda, Simone (Frontiers in Oncology, 2015)
Recent genomic studies revealed a high rate of recurrent mutations in the RAS pathway in primary rhabdomyosarcoma (RMS) samples. In the present study, we therefore investigated how oncogenic RAS mutants impinge on the regulation of cell death of RMS13 cells. Here, we report that ectopic expression of NRAS12V, KRAS12V, or HRAS12V protects RMS13 cells from oxidative stress-induced cell death. RMS13 cells engineered to express NRAS12V, KRAS12V, or HRAS12V were significantly less susceptible to loss of cell viability upon treatment with several oxidative stress inducers including the thioredoxin reductase inhibitor Auranofin, the glutathione (GSH) peroxidase 4 inhibitor RSL3 or Erastin, an inhibitor of the cysteine/glutamate amino acid transporter system xc− that blocks GSH synthesis. Notably, addition of Ferrostatin-1 confers protection against Erastin- or RSL3-induced cytotoxicity, indicating that these compounds trigger ferroptosis, an iron-dependent form of programed cell death. Furthermore, RMS13 cells overexpressing oncogenic RAS mutants are significantly protected against the dual PI3K/mTOR inhibitor PI103, whereas they are similarly sensitive to DNA-damaging drugs such as Doxorubicin or Etoposide. This suggests that oncogenic RAS selectively modulates cell death pathways triggered by cytotoxic stimuli in RMS13 cells. In conclusion, our discovery of an increased resistance to oxidative stress imposed by oncogenic RAS mutants in RMS13 cells has important implications for the development of targeted therapies for RMS.